Magnetic resonance guided adaptive stereotactic body radiotherapy for lung tumors in ultracentral location: the MAGELLAN trial (ARO 2021-3) - Regnery, Sebastian; Ristau, Jonas; Weykamp, Fabian; Hoegen-Saßmannshausen, Philipp; Sprengel, Simon David; Paul, Katharina; Buchele, Carolin; Klüter, Sebastian; Rippke, Carolin; Renkamp, Claudia Katharina; Pohl, Moritz; Meis, Jan; et al. (Radiation oncology, 2022)
Stereotactic Body Radiotherapy (SBRT) is a standard treatment for inoperable primary and secondary lung tumors. In case of ultracentral tumor location, defined as tumor contact with vulnerable mediastinal structures such as the proximal bronchial tree (PBT) or esophagus, SBRT is associated with an increased risk for severe complications. Magnetic resonance (MR)-guided SBRT can mitigate this risk based on gated dose delivery and daily plan adaptation. The MAGELLAN trial aims to find the maximum tolerated dose (MTD) of MR-guided SBRT of ultracentral lung tumors (ULT).
Published 25 May 2022
Gesehen am 06.07.2022